Current collectors including metallized films

A biaxially oriented polymeric substrate with metal layers addresses the issues of adhesion and thermal stability in metal foil current collectors, enhancing safety and energy density in lithium ion batteries.

JP7617312B2Active Publication Date: 2025-01-17MYLAR SPECIALTY FILMS USA LLP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023570035
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-13
Filing Date
2022-05-13
Publication Date
2025-01-17
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

Existing metal foil current collectors in lithium ion batteries face issues such as high electrical conductivity leading to short circuits and thermal runaway, excessive thickness and weight contributing to reduced energy density, and poor adhesion between layers due to high temperature exposure during manufacturing.

Method used

A biaxially oriented polymeric substrate layer with a first and second metal layer, each with a thickness of 1000 nm or less, exhibiting positive thermal expansion at 200°C, providing improved adhesion and peel resistance, and a current collector structure that maintains energy density while preventing excessive current flow.

Benefits of technology

The solution enhances the adhesion between the polymeric substrate and metal layers, maintains energy density, and prevents thermal runaway by acting as an electrochemical fuse, ensuring safe and efficient battery operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617312000005
    Figure 0007617312000005
  • Figure 0007617312000006
    Figure 0007617312000006
  • Figure 0007617312000007
    Figure 0007617312000007
Patent Text Reader

Abstract

A current collector comprising a biaxially oriented polymeric substrate layer and a first metal layer on a surface of the polymeric substrate layer, where the polymeric substrate layer exhibits positive thermal expansion in each of the transverse direction (TD) and the machine direction (MD) at 200° C. in air, the polymeric substrate layer has a thickness of 12 μm or less, and the first metal layer has a thickness of 1000 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polymeric films for use in current collectors, current collectors and other articles made therefrom, and methods of making the same, and in particular to current collectors for use in batteries, especially lithium ion batteries.

[0002] Lithium-ion batteries are widely used in the field of rechargeable batteries, which will continue to grow for the foreseeable future, due in part to the growing demand for consumer electronics and renewable energy storage. In the operation of a battery (i.e., during charging and discharging), lithium ions are transferred between an anode material and a cathode material. Commercially available lithium-ion batteries typically include a metal foil current collector, in which the metal foil is placed in contact with each active solid electrode. Generally, an aluminum-based foil is used as the cathode current collector and placed in contact with the cathode, whereas a copper-based foil is used as the anode current collector and placed in contact with the anode. In some configurations, the cathode material may be coated on the cathode current collector and / or the anode material may be coated on the anode current collector.

[0003] However, such existing metal foil current collectors have problems. First, metal foil current collectors have high electrical conductivity, which can contribute to excessive current flow throughout the battery, leading to short circuits and thermal runaway overheating, and causing fires. Second, metal foil current collectors are relatively thick, dense, and heavy (typically having a thickness greater than 12 μm), and therefore contribute significantly to the overall mass of the battery. To increase energy density and minimize the size and mass of the battery, it is desirable to provide thinner and / or lighter current collectors. However, it is difficult to provide thinner current collectors without adversely affecting their mechanical strength. To that end, metallized polymer film current collectors have been developed. Such current collectors include an insulating or dielectric polymer substrate layer and a conductive metal layer(s) on its surface(s). As known in the art, such current collectors function as electrochemical fuses that break at a given thermal and / or electrical load to avoid excessive current flow and heat runaway. The metal layer is typically formed by a metal deposition process that may require multiple deposition steps. During the metal deposition process, and during subsequent processing of the battery, the current collector (and the polymeric substrate layer within the current collector) are exposed to high temperature conditions for extended periods of time that can cause overheating and permanent damage to the film, such as distortion and wrinkling, and result in loss of adhesion between the metal layer and the polymeric substrate layer.

[0004] It is an object of the present invention to address one or more of the problems mentioned above. In particular, it is an object of the present invention to provide an improved current collector for use in batteries, preferably for use in lithium-ion batteries. A particular object of the present invention is to provide a current collector that exhibits improved adhesion between the polymeric substrate layer and the metal layer(s), especially after exposure to prolonged high temperatures, for example, during manufacture, subsequent processing steps, and / or end use. It is also a particular object of the present invention to provide a current collector that at least maintains, and preferably improves, the energy density of existing metal foil current collectors.

[0005] According to a first aspect of the present invention, there is provided a current collector comprising a biaxially oriented polymeric substrate layer and a first metal layer on a surface of the polymeric substrate layer, the polymeric substrate layer exhibiting a positive thermal expansion in air at 200° C. (and preferably no greater than 3.0%) in each of the transverse direction (TD) and the machine direction (MD), the polymeric substrate layer having a thickness of no greater than 12 μm, and the first metal layer having a thickness of no greater than 1000 nm.

[0006] Preferably, the current collector further comprises a second metal layer, the first metal layer and the second metal layer being on opposite sides of the polymeric substrate layer, and the layer sequence is first metal layer / polymeric substrate layer / second metal layer. If present, the second metal layer has a thickness of 1000 nm or less.

[0007] The inventors have unexpectedly found that such current collectors exhibit excellent delamination resistance between the biaxially oriented polymer substrate layer and the first metal layer and, if present, the second metal layer, even after prolonged exposure to high temperatures, which is particularly advantageous in the field of lithium ion batteries, which are subject to such conditions during manufacture and use.

[0008] The first metal layer, and, if present, the second metal layer, are the outermost layers of the current collector.

[0009] Thus, the current collector comprises at least two layers. Preferably, the first metal layer (A) is disposed directly on the first surface of the polymeric substrate layer (B) to form an AB layer structure, i.e., there is no intervening layer between the metal layer and the polymeric substrate layer, and thus, in this embodiment, the current collector consists of two layers.

[0010] Preferably, the current collector comprises at least three layers: Preferably, a first metal layer (A) is disposed directly on a first surface of a polymeric substrate layer (B) and a second metal layer (C) is disposed directly on a second, opposite surface of the substrate layer to form an ABC layer structure, i.e., there is no intervening layer between the metal layer and the polymeric substrate layer, and thus, in this embodiment, the current collector consists of three layers.

[0011] The substrate layer is a free-standing film, which means a film that can exist independently in the absence of a supporting substrate.

[0012] As used herein, the term polymer refers to a polymer or a copolymer.

[0013] Thermoplastic polymeric materials are preferred. Such materials include homopolymers or copolymers of 1-olefins (e.g. ethylene, propylene and but-1-ene), polyamides, polycarbonates, PVC, PVA, polyacrylates, cellulose and polyesters. Polyolefins and polyesters, especially polyesters, especially linear polyesters, are preferred.

[0014] The term polyester as used herein refers to homopolyesters or copolyesters derived from one or more diols, at least one of which is an aliphatic diol, and one or more dicarboxylic acids, at least one of which is an aromatic dicarboxylic acid. Suitable dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 2,5-, 2,6- or 2,7-naphthalenedicarboxylic acid, succinic acid, sebacic acid, adipic acid, azelaic acid, 4,4'-diphenyldicarboxylic acid, hexahydroterephthalic acid or 1,2-bis-p-carboxyphenoxyethane (optionally with a monocarboxylic acid such as pivalic acid). Suitable diols include aliphatic and cycloaliphatic diols, such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol and 1,4-cyclohexanedimethanol. Preferably, the aromatic dicarboxylic acid is selected from terephthalic acid and 2,5-, 2,6- or 2,7-naphthalenedicarboxylic acid, preferably terephthalic acid and 2,6-naphthalenedicarboxylic acid. Preferably, the aliphatic diol is ethylene glycol. Preferably, the polyester is a homopolyester.

[0015] Preferred polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) polyesters may optionally contain relatively small amounts (preferably less than 10% or less than 5% by weight) of one or more residues derived from other dicarboxylic acids and / or diols as one or more comonomers, such as isophthalic acid, phthalic acid, 1,4-, 2,5-, or 2,7-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, hexahydroterephthalic acid, 1,10-decanedicarboxylic acid, and dicarboxylic acids of the general formula C n H 2n Aliphatic dicarboxylic acids of (COOH)2 (n=2-8), such as succinic acid, glutaric acid, sebacic acid, adipic acid, azelaic acid, suberic acid or pimelic acid. Other diols include aliphatic and cycloaliphatic glycols, such as diethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. Preferably, the polyester contains only one dicarboxylic acid, i.e., terephthalic acid or 2,6-naphthalenedicarboxylic acid, preferably terephthalic acid. Preferably, the polyester contains only one diol, i.e., ethylene glycol.

[0016] Preferred polyolefins are selected from polyethylene or polypropylene, preferably polypropylene.

[0017] Preferred polyamides are linear aliphatic polyamides, preferably selected from nylon 6,6, nylon 6, nylon 6.66, nylon 6,10, nylon 6,4, and blends and mixtures thereof. Nylon 6 and nylon 6,6 are particularly preferred polyamides, with nylon 6,6 being most preferred.

[0018] Preferably, the polymeric substrate layer is a PET or PEN film.

[0019] The polymer is the major component of the polymeric substrate layer and comprises at least 60% by weight, preferably at least 70% by weight, preferably at least 80% by weight of the total weight of the polymeric substrate layer. For example, the polymer may comprise at least 85% by weight, at least 90% by weight, or at least 95% by weight of the total weight of the polymeric substrate layer.

[0020] The polymer substrate layer may further include other additives that are commonly used in the manufacture of polymer films. Such conventional additives may be present in minor proportions, typically 35% by weight or less, typically 20% by weight or less, typically 5% by weight or less, typically 2% by weight or less, based on the total weight of the layer. Thus, agents such as particulate fillers, hydrolysis stabilizers, antioxidants, UV stabilizers, crosslinkers, dyes, lubricants, radical scavengers, heat stabilizers, surfactants, slip aids, antiblocking agents, flame retardants, gloss enhancers, antidegradants, viscosity modifiers, and dispersion stabilizers may be incorporated as appropriate. It is well known in the art that particulate fillers are particularly useful for improving handling and winding during manufacture. Particulate fillers are typically particulate inorganic fillers (e.g., calcium carbonate, clay, silica, zeolite, silicone beads (e.g., functionalized polydimethylsiloxane), dicalcium phosphate, tricalcium phosphate, cenospheres, zeospheres, talc, titanium dioxide, barium sulfate, and barium titanate). The filler particle size distribution can be unimodal, bimodal, and trimodal. Preferably, the volume weighted average particle size (D (4,3) ) is in the range of 0.1 to 10 μm for unimodal, bimodal and trimodal distributions. Preferably, the filler particle size distribution is bimodal such that there are two maximum peaks. Preferably, the maximum of the first particles is a volume weighted mean particle size (D) of about 0.5±0.3 μm. (4,3) ) and the maximum value of the second particle is a volume weighted mean particle size (D (4,3) ). The particle size of the filler particles is suitably measured by diffraction of laser light. The particulate inorganic filler is present in relatively small amounts, typically less than 5.0% by weight, typically less than 2.0% by weight, typically less than 1.0% by weight.

[0021] Formation of the polymer is readily accomplished by conventional synthetic methods well known in the art. For example, polyesters can be produced by a first step of direct esterification or transesterification, followed by a second step of polycondensation. Preferably, the synthetic procedure further comprises a solid-state polymerization (SSP) step to increase the molecular weight of the polymer, as is well known in the art. Suitable solid-state polymerization techniques are disclosed, for example, in EP-A-0419400, the disclosure of which is incorporated herein by reference. Thus, SSP typically involves increasing the crystalline melting point (T M ) is 10 to 50°C lower than the glass transition temperature (T g ) (or above the highest glass transition temperature if the polyester exhibits multiple glass transition temperatures). An inert atmosphere of dry nitrogen or vacuum is used to prevent degradation. In a preferred embodiment, the solid state polymerization is carried out at 220° C. under vacuum for 16 hours.

[0022] Polyesters suitable for use in the present invention have an intrinsic viscosity of at least 0.5 dL / g, preferably at least 0.55 dL / g, preferably at least 0.6 dL / g, preferably at least 0.7 dL / g, preferably at least 0.8 dL / g.

[0023] The polymeric substrate layer is preferably a monolayer film.

[0024] Advantageously, the films can be, and preferably are, produced in air, i.e., the films are not produced (including the extrusion, casting and stretching steps) under an atmosphere of inert gas (e.g., nitrogen, or a noble gas such as argon).Thus, the polymer compositions and films described herein are thermally stable and do not require special handling conditions, particularly an inert atmosphere, during production or storage.

[0025] The formation of the membrane may be carried out by conventional extrusion techniques well known in the art. In general, the process involves extruding a layer of molten polymer within a range appropriate for the melting temperature of the polymer, for example, about 270 to about 300°C (or typically not more than about 15°C, preferably not more than about 10°C, above the crystalline melting point of the polymer), and then quenching the extrudate to ensure that the polymer is quenched to an amorphous state. The quenched extrudate is then biaxially oriented by stretching in two mutually perpendicular directions in the plane of the film at a temperature above the glass transition temperature(s) of the polymer to achieve a sufficient combination of mechanical and physical properties. Biaxial orientation may be achieved by sequential or simultaneous biaxial orientation. In the present invention, the film is advantageously produced by simultaneous biaxial orientation, for example in a tubular process, by extruding a thermoplastic polymer tube, which is subsequently quenched, reheated, and then expanded by internal gas pressure to cause transverse orientation and drawn at a speed to cause longitudinal orientation. Particularly suitable simultaneous biaxial orientation processes are disclosed in EP-2108673-A and US-2009 / 0117362-A1, the disclosures of which are incorporated herein by reference.

[0026] Stretching is typically carried out so that the dimensions of the oriented film are 2 to 7, preferably 2 to 5, more preferably 2.5 to 4.5, more preferably 3.0 to 4.5, more preferably 3.0 to 4.0 times its original dimensions in each direction of stretching. Preferably, the film is stretched 3.2 to 3.6 times its original dimensions in the machine direction (MD) and preferably 3.3 to 3.8 times its original dimensions in the transverse direction (TD). Stretching is performed to reduce the T of the polymer composition. g A higher temperature, preferably T g At least about 5° C. higher, preferably at least about 15° C. higher, preferably about T g +5℃~approx.T g +75°C, preferably around T g +5℃~T g+30°C. Thus, the stretching is usually carried out at a temperature in the range of about 5 to about 155°C, preferably about 5 to about 145°C. When the polymer composition is PET, the stretching is usually carried out at a temperature in the range of about 85 to about 110°C, preferably about 95 to about 100°C. When the polymer composition is PEN, the stretching is usually carried out at a temperature in the range of about 130 to about 155°C, preferably about 140 to about 145°C. It is not necessary to stretch equally in the machine direction and the transverse direction, but this is preferred when balanced properties are desired.

[0027] The stretched film is then dimensionally stabilized. In a first step, the film is annealed under a dimensional support (or restraining means) to induce the desired crystallinity in the polymer. A temperature of at least about 200° C. is preferred. Preferably, the temperature used is above the glass transition temperature(s) of the polymer, but below its melting temperature (T M Within these constraints, the preferred annealing temperature is typically about 80° C. below the melting temperature of the film (i.e., T M -80℃)~T M 10°C lower than the temperature (i.e., T M −10° C.), preferably at about T M -70℃~approx.T M The annealing temperature is therefore suitably in the range of about 200 to about 245° C., preferably about 215 to about 245° C., preferably about 220 to about 245° C., preferably about 220 to about 240° C. The time for which the film is held at this temperature is preferably in the range of 0 to 60 seconds, preferably 0.1 to 10 seconds, preferably 0.5 to 5 seconds, preferably 0.7 to 3 seconds.

[0028] After annealing under dimensional constraint, the film undergoes dimensional relaxation in both transverse direction (TD) and machine direction (MD). Dimensional relaxation can be accomplished sequentially or simultaneously, preferably sequentially. The relaxation step is preferably an in-line relaxation step, i.e., a step in the film production line. The film relaxes by about 0.5 to about 5.0%, preferably about 1.0 to about 4.0%, preferably about 1.0 to 3.0%, preferably about 1.0 to about 2.0% in each of the transverse direction (TD) and machine direction (MD). The degree of relaxation in the machine direction and the transverse direction can be the same. However, if balanced properties are desired, it is preferred that the degree of relaxation in the machine direction and the transverse direction are not the same. In the relaxation step, the film is preferably heated to a temperature below that of the immediately preceding annealing step, and lower MD and TD tensions are used. MD relaxation is controlled by slowing down the film line speed, and TD relaxation is controlled by decreasing the distance between the film clamps on the opposing side edges of the film, each resulting in a reduction in the tension that a film of the relevant dimensions is subjected to at this stage of production. A temperature of at least about 200°C is preferred, preferably about 200°C to about 250°C, preferably about 200°C to about 245°C, preferably about 200°C to about 240°C, preferably about 210°C to about 230°C, preferably about 215°C to about 230°C, preferably about 215°C to about 225°C. The heating time for the relaxation step depends on the temperature used, but is usually in the range of 0 to 30 seconds, preferably 0.1 to 10 seconds, preferably 0.4 to 4 seconds, preferably 0.9 to 3.8 seconds.

[0029] Then, preferably, a second relaxation step is carried out (in this case, the above relaxation step is referred to as a first relaxation step). The second relaxation step is carried out in a manner similar to that described for the first relaxation step. A temperature of at least about 195°C is preferred, and a temperature of at least about 200°C is most preferred. The second relaxation step may be carried out at a temperature similar to that of the first relaxation step. Alternatively, the second relaxation step may be carried out at a lower temperature than the first relaxation step, preferably at least about 5°C lower. Thus, preferably, the second relaxation step is carried out in the range of about 195°C to about 245°C, preferably about 195°C to about 240°C, preferably about 195°C to about 235°C, preferably about 195°C to about 230°C, preferably about 195°C to about 220°C, preferably about 195°C to about 215°C. The heating time in the second relaxation step depends on the temperature used, but is usually in the range of 0 to 30 seconds, preferably 0.1 to 10 seconds, preferably 0.4 to 3.5 seconds, preferably 0.7 to 3.0 seconds.

[0030] After the annealing and relaxation step(s), the film is rapidly cooled.

[0031] The inventors have found that the resulting polymer film exhibits high dimensional stability at high temperatures and positive thermal expansion in each of the transverse (TD) and machine direction (MD) at 200° C. Thus, the thermal response of the polymer substrate layer in each of the machine direction and machine direction matches that of the metal layer(s), and the current collector of the present invention exhibits high dimensional stability without deformation, warping or delamination during subsequent processing at high temperatures (e.g., during metal deposition or subsequent cell formation). In contrast, prior art current collectors in which the polymer substrate layer is not manufactured using the annealing and relaxation process described herein exhibit shrinkage and dimensional instability, with deformation and warping observed during subsequent processing at high temperatures and poor delamination resistance.

[0032] Preferably, the polymer substrate layer exhibits a thermal expansion in air of >0% to 3.0%, preferably >0% to 2.0%, preferably 0.1% to 2.0%, preferably 0.2% to 1.5% in each of the transverse direction (TD) and machine direction (MD) in air at 200° C. Preferably, the polymer substrate layer exhibits an isotropic thermal expansion, i.e. the layer expands by the same amount in TD and MD.

[0033] The inventors have found that the manufacturing process, particularly the annealing and relaxation process described herein, can be carried out so that the polymer substrate film exhibits isotropic thermal expansion.In particular, the degree of dimensional relaxation in MD and TD in the relaxation process described herein can be controlled.For example, the degree of dimensional relaxation that occurs in MD and TD can be different to counter the residual deformation in MD or TD resulting from previous manufacturing steps, so that the final polymer film exhibits balanced properties and therefore exhibits isotropic thermal expansion.

[0034] Preferably, the polymer substrate layer has a positive coefficient of linear thermal expansion (CLTE) in air over the range of 32° C. to 200° C., preferably 20×10 in each of the transverse direction (TD) and machine direction (MD). -5 Positive CLTE less than 17 x 10 / °C, preferably -5 Positive CLTE less than 10 x 10 / °C, preferably -5 Positive CLTE less than 9 x 10 / °C, preferably -5 Positive CLTE less than 8.5 x 10 / °C, preferably -5 / °C.

[0035] The thickness of the polymer substrate layer is 12.0 μm or less, preferably 10.0 μm or less, preferably 8.0 μm or less, preferably 6.0 μm or less. The thickness of the polymer substrate layer is preferably at least 1.0 μm, preferably at least 2.0 μm, preferably at least 3.0 μm, preferably at least 4.0 μm. Thus, the thickness of the polymer substrate layer is preferably 1.0 to 12.0 μm, preferably 2.0 to 8.0 μm, preferably 4.0 to 8.0 μm, preferably 4.0 to about 6.0 μm.

[0036] The first metal layer and, if present, the second metal layer are each formed from a metallic conductive material. Preferably, the first and second metal layers comprise the same metallic conductive material. Alternatively, the first metal layer and the second metal layer may comprise different metallic conductive materials. The metallic conductive material is preferably selected from at least one of aluminum, copper, nickel, titanium, silver, nickel-copper alloy, or aluminum-zirconium alloy. Preferably, the metallic conductive material is aluminum or copper. When the current collector is a cathode current collector, the first metal layer and, if present, the second metal layer preferably comprise aluminum. When the current collector is an anode current collector, the first metal layer and, if present, the second metal layer preferably comprise copper.

[0037] When the first metal layer and, if present, the second metal layer comprise aluminum, the polymeric substrate layer is preferably a PET film.When the first metal layer and, if present, the second metal layer comprise copper, the polymeric substrate layer is preferably a PEN film.

[0038] The metal layer(s) preferably comprises at least 90% by weight, preferably at least 95% by weight, preferably at least 98% by weight, preferably at least 99% by weight of the metallic conductive material described above, the stated weights of the metallic conductive material being weight percentages relative to the total weight of the metallic layer. In a preferred embodiment, the metallic layer consists of the metallic conductive material.

[0039] The metal layer(s) exhibit a positive coefficient of thermal expansion. Preferably, the first metal layer and, if present, the second metal layer in the current collector of the present invention, independently exhibit a thermal expansion in air at 200°C of greater than 0% to 2.0%, preferably greater than 0% to 1.0%, preferably 0.25% to 0.75%, preferably 0.3% to 0.5%. Each metal layer in the current collector of the present invention preferably exhibits an isotropic thermal expansion, i.e., the layers expand by the same amount in orthogonal directions, e.g., directions corresponding to the longitudinal and transverse directions of the polymeric substrate layer. Preferably, the first metal layer and the second metal layer exhibit the same expansion as each other at 200°C.

[0040] Preferably, the ratio of the thermal expansion in air at 200°C in the lateral direction of the polymeric substrate layer to the thermal expansion in air at 200°C of each of the first and second metal layers is 1:5 to 5:1, preferably 2:1 to 1:2, preferably 1.5:1 to 1:1.5, preferably 1.2:1 to 1:1.2:1, preferably about 1:1.

[0041] Preferably, the ratio of the thermal expansion in the longitudinal direction of the polymer substrate layer in air at 200°C to the thermal expansion in air of each of the first and second metal layers at 200°C is 1:5 to 5:1, preferably 1.5:1 to 1:1.5, preferably 1.2:1 to 1:1.2, preferably about 1:1.

[0042] Preferably, the first metal layer, and, if present, the second metal layer, independently, have a melting point of about 10×10 in air at 100° C. -6 / ℃ ~ approx. 30×10 -6 / °C, preferably about 12 x 10 -6 / ℃ ~ approx. 18×10 -6 The positive coefficient of linear thermal expansion (CLTE) is shown in / °C.

[0043] Preferably, the thickness of the first metal layer, and, if present, the second metal layer, are each independently in the range of about 50 nm to about 1000 nm, preferably about 100 nm to about 1000 nm, preferably about 100 nm to about 800 nm, preferably about 150 nm to about 700 nm.

[0044] The first metal layer and, if present, the second metal layer are each appropriately deposited on the polymer substrate layer. Any suitable deposition technique known in the art for producing metallized films can be used, including at least one of vapor deposition and electroless plating. Preferably, the first metal layer and the second metal layer are independently deposited on the polymer substrate layer by at least one of vapor deposition and electroless plating. The vapor deposition can be at least one of physical vapor deposition (PVD), virtual cathodic deposition (VCD) or chemical vapor deposition (CVD).

[0045] Preferably, the physical vapor deposition is selected from at least one of evaporative deposition and sputtering deposition. The evaporative deposition is preferably at least one of vacuum evaporation, thermal evaporation, or electron beam evaporation techniques. The sputtering deposition is preferably magnetron sputtering. Suitable processes include, for example, plasma-assisted deposition techniques, such as plasma-assisted electron beam evaporation techniques, and plasma-assisted sputtering techniques.

[0046] Preferably, thermal evaporative deposition, electron beam evaporation, or virtual cathode evaporation is used to deposit the metal layer(s).

[0047] Typically, thermal evaporation deposition involves placing a polymer substrate and a source material in a vacuum chamber. The source material is heated under vacuum (preferably for 10 -4 The vaporized feedstock particles are heated under a pressure of less than 100 Pa and at high temperatures. The vaporized feedstock particles disperse towards the substrate and condense on the substrate surface to form a thin film. A large direct current (preferably in the range of 100-150 mA for 10-15 seconds) is applied to a resistive coil, typically in the form of a powder or solid bar, which generates the heat used to vaporize the feedstock. Suitable devices include those commercially available from Balzers AG (Liechtenstein) under the designation "BAE370" or from Buhler and Applied Materials.

[0048] Typically, electron beam evaporation involves evaporating a material with an intense beam of high-energy electrons. A hot filament is used to thermionic emit electrons, which are accelerated to evaporate the material.

[0049] Typically, virtual cathode deposition is performed using a high energy density electron beam (preferably with an energy of 100 MW / cm 2 The high energy density electron beam ablates the solid target, resulting in a portion of the ablated target material (e.g., about 0.001 mm2). 3 ) forms a plasma. The plasma propagates towards the polymer substrate in the form of a plasma flume. The plasma flume can have a speed of up to about 50 km / sec. The plasma of the target material condenses on the substrate surface to form a thin film. For example, 2 Thin films up to 0.1 nm thick can be formed per pulse at 100 Hz. By repeating high voltage pulses (e.g., frequencies up to about 600 Hz) and / or using an apparatus including multiple virtual cathodes, the deposited film can be grown until a desired thickness is reached. Suitable virtual cathode deposition methods and apparatus are known and include, for example, those discussed in WO-2016 / 042530-A and US-2020 / 0095129-A, the disclosures of which are incorporated herein by reference.

[0050] The deposition technique may require a single pass or multiple passes (e.g., double passes) to deposit a metal layer of the desired thickness. Preferably, the deposition technique requires a single pass, which advantageously increases manufacturing efficiency and minimizes prolonged exposure of the polymer substrate to high temperature conditions.

[0051] As will be appreciated by those skilled in the art, a current collector is required to exhibit electrical conductivity when placed in a battery. Thus, electrical conductivity must be permitted between the outer surfaces of the current collector, despite the electrical insulation provided by the polymeric substrate layer. For example, electrical conductivity must be permitted from the first metal layer to the second metal layer (if present), despite the electrical insulation provided by the polymeric substrate layer placed between the first and second metal layers.

[0052] In one embodiment, referred to herein as configuration 1, the current collector further comprises at least one conductive tab connecting the first metal layer and the second metal layer such that the current collector is electrically conductive from one surface of the current collector to the other surface of the current collector. Such conductive tabs are known in the art and are disclosed, for example, in WO-2019 / 051123-A and US-10700339-B. Preferably, the tab extends beyond the periphery of the current collector such that the current collector can be connected to other components within the battery. Preferably, the tab extends from the interior to the exterior of the lithium ion battery such that the tab can connect the battery to an external power source.

[0053] In another embodiment, referred to herein as configuration 2, the polymer substrate layer includes a channel extending from a first surface to an opposite second surface, (i) both sides of the channel are at least partially coated with at least one metal, and / or (ii) the channel is at least partially filled with at least one metal, preferably creating a conductive pathway between the first and second metal layers. Such channels are known in the art and are disclosed, for example, in US-2019 / 0305320-A. The channel may have an opening size (e.g., diameter) ranging from about 1 μm to about 5 mm. The percentage of the surface area of ​​the polymer substrate layer that is made up of channel openings is typically about 0.01 to about 10%. Such channels can further reduce the weight of the battery and can improve electrochemical properties such as charge / discharge rates and cycle life. The metal is preferably deposited during the metal deposition step(s) used to deposit the first and second metal layers described above, preferably during a virtual cathode deposition technique. Configuration 2 is further illustrated in FIG. 1. FIG. 1A shows a cross-sectional view of the current collector configuration. The current collector (10) has a biaxially textured substrate layer (B) (3), a first metal layer (A) (1), and a second metal layer (C) (2), with the current collector having an ABC layer structure. The substrate layer (B) has a plurality of perforations filled with metal (4). The metal forms a continuous connection between the first metal layer (A) and the second metal layer (C). FIG. 1B shows the substrate layer (B) in the current collector configuration in top view.

[0054] Configuration 1 and Configuration 2 may be present in the same battery.

[0055] The total thickness of the current collector of the present invention is preferably about 1 μm to about 12 μm, preferably about 2 μm to about 8 μm, preferably about 4 μm to about 8 μm, preferably about 4 to about 6 μm.

[0056] Preferably, the current collector has a resistance of about 2.0 Ωsq -1 Less than or equal to 1.5Ωsq, preferably about 1.5Ωsq -1 Less than 1.0Ωsq, preferably about 1.0Ωsq -1 Preferably, the current collector exhibits a sheet resistance of at least about 0.01 Ωsq.-1 , preferably at least about 0.02 Ωsq -1 , preferably at least about 0.05 Ωsq -1 Preferably, the current collector exhibits a sheet resistance of about 0.01 Ωsq. -1 ~ approx. 2.0Ωsq -1 , preferably about 0.02Ωsq -1 ~ approx. 2.0Ωsq -1 , preferably about 0.02Ωsq -1 ~about 1.5Ωsq -1 , preferably about 0.05Ωsq -1 ~ approx. 1.0Ωsq -1 The sheet resistance of

[0057] Preferably, the current collector exhibits a breakdown current of about 35 A or less, preferably about 30 A or less, preferably about 20 A or less, preferably about 10 A or less, preferably about 5 A or less. Preferably, the current collector exhibits a breakdown temperature of about 300° C. or less, preferably about 250° C. or less, preferably about 240° C. or less, preferably about 230° C. or less, preferably about 220° C. or less. In a preferred embodiment, the breakdown temperature is less than the crystalline melting point (T M ) or less, which typically corresponds to the point at which the polymer layer begins to shrink. Thus, when the polymer substrate layer is a PEN film, the current collector preferably exhibits a breakdown temperature of about 270° C. or less, preferably about 260° C. or less, preferably about 250° C. or less, preferably about 220° C. or less. When the polymer substrate layer is a PET film, the current collector preferably exhibits a breakdown temperature of about 260° C. or less, preferably about 250° C. or less, preferably about 220° C. or less. The breakdown current and temperature corresponds to the point at which the current collector fails, i.e., the film acts as an electrochemical fuse to successfully prevent excessive current flow and risk of heat propagation within the battery.

[0058] Preferably, the adhesive strength between the metal layer and the polymeric substrate layer is at least 600 g / 25 mm, preferably at least about 700 g / 25 mm, preferably at least about 800 g / 25 mm.

[0059] According to a second aspect of the present invention there is provided a method of manufacturing a current collector as described herein, the method comprising the steps of: (i) forming a biaxially oriented polymeric substrate layer; and (ii) depositing a metal onto the first surface of the substrate layer to form a first metal layer.

[0060] Preferably, the method comprises the steps of: (iii) depositing a metal on a second surface of the substrate layer to form a second metal layer; The layer sequence is thereby first metal layer / polymeric substrate layer / second metal layer.

[0061] Prior to applying the metal layer, the exposed surface of the biaxially oriented polymeric substrate layer may, if necessary, be subjected to a chemical or physical surface modification treatment to improve the bond between the polymeric substrate layer and the subsequently applied layer. It is particularly advantageous to subject the exposed surface of the polymeric substrate layer to such a treatment prior to depositing the metal layer.

[0062] A preferred treatment is to subject the exposed surface of the substrate layer to a plasma treatment. Plasma treatment involves exposing the surface to an electrical discharge, a so-called glow discharge, which is generated and maintained by applying a high voltage in a low pressure gas atmosphere. The surface is treated with active particles of electrons, ions, excited atoms, excited molecules, radicals, and ultraviolet light, which are formed during the glow discharge. One or more agents known in the art can be injected into the glow discharge and onto the substrate. One or more agents can be deposited to form a coating on the exposed surface. Well-known agents include organic molecules, inorganic molecules, and biomolecules. Preferred agents include a mixture of acrylic acid and methacrylic anhydride, (3-glycidyloxypropyl)trimethoxysilane, N-(3-trimethoxysilylpropyl)diethylenetriamine, or (3-mercaptopropyl)trimethoxysilane. For example, suitable mixtures of acrylic acid and methacrylic anhydride include mixtures containing 75% by weight acrylic acid and 25% by weight methacrylic anhydride, or mixtures containing 50% by weight acrylic acid and 50% by weight methacrylic anhydride.

[0063] A preferred plasma treatment is corona treatment (sometimes referred to as air plasma), in which a high voltage electrical stress accompanied by corona discharge is applied to the exposed surface of the polymeric substrate layer. The preferred treatment by corona discharge may be carried out in air at atmospheric pressure using conventional equipment, preferably using a high frequency high voltage generator having a power output of 1-20 kW at a potential of 1-100 kV. Discharge is conventionally achieved at a discharge station by passing the film over a dielectric support roller at a linear speed preferably of 1.0-500 m per minute. The discharge electrode may be located 0.1-10.0 mm from the moving film surface.

[0064] After plasma treatment, the polymeric substrate layer preferably exhibits a water contact angle of about 70° or less, preferably about 65° or less, preferably about 60° or less. After plasma treatment, the polymeric substrate layer preferably exhibits a water contact angle of at least about 5°, preferably at least about 10°, preferably at least about 14°. Preferably, after plasma treatment, the polymeric substrate layer exhibits a water contact angle of about 5° to about 70°, preferably about 10° to about 65°, preferably about 14° to about 60°.

[0065] The water contact angle between a droplet of HPLC grade water and the polymer substrate layer can be measured by a Surface Analyst 3001 (BTG Labs).

[0066] After plasma treatment, the polymeric substrate layer preferably exhibits a surface energy of about 30 mN / m to about 100 mN / m, preferably about 30 to about 80 mN / m. The surface energy can be measured by an ink-based surface energy test, such as the dyne level test according to ISO 8296.

[0067] The descriptions and preferences for the first embodiment apply equally to the second embodiment.

[0068] According to a third aspect of the present invention, there is provided the use of a biaxially oriented polymer film as a substrate in a current collector further comprising a first metal layer, said use for imparting improved adhesive strength and / or peel resistance between said substrate and a metal layer, said biaxially oriented polymer substrate layer exhibiting positive thermal expansion in air at 200° C. in each of the transverse direction (TD) and the machine direction (MD), said polymer substrate layer having a thickness of 12 μm or less, and said first metal layer having a thickness of 1000 nm or less.

[0069] Preferably, the current collector further comprises a second metal layer, the current collector layers having a sequence of first metal layer / polymeric substrate layer / second metal layer, and the second metal layer having a thickness of 1000 nm or less.

[0070] The descriptions and preferences of the first and second aspects apply equally to the third aspect.

[0071] According to a fourth aspect of the invention, there is provided a battery comprising an anode material, an anode current collector, a cathode material, a cathode current collector, and a separator disposed between the anode material and the cathode material, wherein at least one of the current collectors is a current collector described herein.

[0072] The battery may be selected from a lithium ion battery, a lithium sulfur (LiS) battery, a lithium air (LiO2) battery or a sodium ion battery. Preferably, the battery is a lithium ion battery, a lithium sulfur (LiS) battery or a lithium air (LiO2) battery. Preferably, the battery is a lithium ion battery. Preferably, the battery is a sodium ion battery.

[0073] Any suitable anode material, cathode material, and separator as are conventional in the art may be used.

[0074] The anode material may be selected from graphite and / or lithium titanate (LTO).

[0075] The cathode material may be selected from lithium or mixed oxides of lithium with other metal(s), in particular lithium titanate (LTO), lithium iron phosphate (LiFePO4, also known as LFP) and / or lithium nickel-manganese-cobalt oxide (LiNiMnCoO2, also known as NMC).

[0076] The separator can be a polymer, ceramic, nonwoven, or woven separator. Suitable polymer separators are disclosed, for example, in WO-2019 / 186173-A and WO-2021 / 064359-A, the disclosures of which are incorporated herein by reference.

[0077] The battery, preferably a lithium ion battery, may further include an electrolyte, which, if present, is preferably a conductive organic solvent that may saturate the other materials present in the battery, thereby providing a mechanism for ions to be conducted between the anode and cathode.

[0078] Alternatively, the battery (preferably a lithium-ion battery) can be a dry cell, which comprises a solid separator between the anode and cathode materials, which acts as both the separator and the electrolyte, thereby eliminating the need for a liquid electrolyte.

[0079] In the embodiment of configuration 1 described above, the current collector further includes at least one conductive tab connecting the first metal layer and the second metal layer such that the current collector is electrically conductive from one surface of the current collector to the other surface of the current collector. Preferably, the tab extends beyond the periphery of the current collector such that the current collector can be connected to other components within the battery. Preferably, the tab extends from the interior to the exterior of the battery such that the tab can connect the battery to an external power source.

[0080] Preferably, the electrode material is coated or otherwise deposited onto a current collector.

[0081] The batteries (preferably lithium ion batteries) may have any configuration known in the art, including cans, pouch cells, prismatic cells, coin cells, cylindrical cells, wound prismatic cells, and wound pouch cells.

[0082] The explanations and preferences for the first to third aspects apply equally to the fourth aspect.

[0083] According to a fifth aspect of the present invention there is provided the use of a current collector as described herein in a battery as described herein (preferably a lithium ion battery).

[0084] The explanations and preferences for the first to fourth aspects apply equally to the fifth aspect.

[0085] According to a sixth aspect of the present invention there is provided a method of manufacturing a battery as described herein (preferably a lithium ion battery), the method comprising the steps of: (i) preparing a current collector as described herein; (ii) assembling a battery (preferably a lithium ion battery), the battery comprising an anode material, a cathode material, a separator between the anode and cathode materials, an anode current collector, and a cathode current collector, at least one of the current collectors being the current collector obtained from step (i).

[0086] Preferably, the anode or cathode material can be coated or deposited on the current collector described herein using any suitable coating or deposition technique conventionally used in the art for electrode preparation. It will be understood that the anode material is coated or otherwise deposited on the outer surface of the metal layer of the anode current collector, whereas the cathode material is coated or otherwise deposited on the outer surface of the metal layer of the cathode current collector. During this coating or deposition process, high processing temperatures (e.g., about 200° C.) are used. In a preferred embodiment, the electrode material is coated on the current collector.

[0087] The electrode / current collector assembly is suitably dried at a temperature of about 50° C. to about 170° C., preferably about 80° C. to 160° C. It will be appreciated that the drying step may include a variety of different temperature zones with appropriate heating profiles.

[0088] The dried electrode / current collector assembly is preferably compacted, for example by calendering between a pair of rotating rollers. During calendering, the assembly is subjected to electrostatic discharge and may be cleaned, for example, by brushing or air flow. Optionally, all or part of the compaction step may be heated, for example, by preheating sections and / or rollers in the calendering process, for example, to a temperature of about 50° C. to about 250° C.

[0089] The explanations and preferences for the first to fifth aspects apply equally to the sixth aspect. The invention will be further explained with reference to the drawings as described below. [Brief description of the drawings]

[0090] [Figure 1] 1 shows the assembly of a current collector according to configuration 2, as described above. A shows a cross-sectional view of the current collector. B shows the substrate layer (B) in the current collector configuration in top view. [Figure 2A] As discussed below, a TGA plot of the thermal relaxation of Example 5 from about 25° C. to about 200° C. is shown. [Figure 2B] As discussed below, a TGA plot of the thermal relaxation of Example 6 from about 25° C. to about 200° C. is shown. [Figure 2C] As discussed below, a TGA plot of the thermal relaxation of Example 7 from about 25° C. to about 200° C. is shown.

[0091] Characteristic measurements The following test methods were used to evaluate the properties of the current collectors and cells described herein.

[0092] (i) Expansion of a biaxially oriented polymer layer Samples of the biaxially oriented polymer layers with dimensions of 5 mm x 8 mm were subjected to thermomechanical analysis using a thermomechanical analyzer (TMA Q400 from TA Instruments Inc.). The longer dimension of the sample (i.e., the 8 mm dimension) corresponds to the sample direction in which expansion was tested. The samples were mounted in the instrument and subjected to a strain of 1 N / mm in either the machine direction (MD) or the transverse direction (TD). 2and a heating rate of 10°C / min from 32°C to 220°C. Thermal expansion in air was measured at a temperature of 200°C. Thermal expansion in air at 200°C is defined as the % change in the dimension of the film in a given direction (i.e., MD or TD) and was calculated as (L1-L0) / L0x100, where L0 is the dimension at 32°C and L1 is the dimension at 200°C. As will be appreciated by those skilled in the art, a negative thermal expansion indicates thermal contraction.

[0093] (ii) Coefficient of linear thermal expansion (CLTE) The same method as in (i) was used. For the linear thermal expansion coefficient (b), the CLTE value was obtained from the following equation: CLTE = (L1-L0) / (L0 x (T2-T1)) where (L1-L0) is the measured change in length of the sample over the temperature range (T2-T1) and L0 is the original sample length at 32° C. Preferably, T2 was 200° C. and T1 was 32° C. This data can be plotted as a function of the % change in specimen length with temperature, normalized to 32° C.

[0094] (iii) Sheet resistance The sheet resistance of the conductive layer was measured using a linear four-point probe (Jandel model RM2) according to ASTM F390-98 (2003).

[0095] (iv) Breakdown current and temperature at breakdown A current collector sample having dimensions of 50 mm x 10 mm was held between a pair of conductive clamps at each end. 2 The sample was clamped so that the tensile strength of the specimen was held within the clamp. A current was passed through the sample at a heating rate of 2 A / min until breakdown was observed. The temperature profile of the sample was monitored throughout the test using a thermal imaging camera to determine the temperature at breakdown.

[0096] (v) Adhesion strength of current collector The adhesive strength of the metallized polymer substrate to EAA (ethylene acrylic acid film) (available as Vistafix (TP) from UCB Sidac Division) having a thickness of 25 μm was evaluated as follows: A sample of the current collector and a sample of the EAA film were placed together such that the outer surface of the metallized polymer substrate layer was in contact with the surface of the EAA film. The samples were heat sealed for 10 seconds at 105° C. (upper jaw) and 25° C. (lower jaw) under 50 psi pressure using a Sentinel Model 12 (Packaging Industries Group Inc.) machine. The sealed samples were cut into 25 mm wide strips and the adhesive strength was determined using an Instron Model 4464. The jaws were set 50 mm apart. The upper jaw was raised at a rate of 300 mm / min holding the EAA piece of the sealed sample and the lower jaw was stationary holding the current collector piece of the sealed sample. The average peel force was measured and reported as the average of five results. The plane of adhesive failure was also noted.

[0097] If the adhesive strength between the metal layer and the polymeric substrate layer is lower than that between the metal layer and the EEA film (about 800 g / 25 mm), the test sample peels along the interface between the metal layer and the polymeric substrate layer, in which case the average peel force represents the adhesive strength between the metal layer and the polymeric substrate layer.

[0098] When the adhesive strength between the metal layer and the polymer substrate layer is higher than the adhesive strength between the metal layer and the EEA film (800 g / 25 mm), the test sample peels off along the interface between the metal layer and the EEA film.

[0099] Another failure mode is coherent failure within the metallized layer itself, which also indicates that the adhesive strength between the metal layer and the polymer substrate layer is greater than the force required to achieve coherent failure (typically, the adhesive strength between the metal layer and the polymer substrate layer is therefore greater than about 800 g / 25 mm).

[0100] (vi) Resistance to peeling of current collector Peel resistance was evaluated by exposing the current collector to high temperatures by placing it in a heated oven, i.e., 200° C. for 5 or 10 minutes, followed by 130° C. for the same 5 or 10 minutes. Adhesion strength was measured according to the method described above before and after said heat treatment to evaluate the peel resistance of the current collector after exposure to high temperature conditions representative of those used during a typical battery manufacturing process. Peel resistance is defined as follows: Peel resistance = 100*((A TT -A0) / A0) During the ceremony, A TT = Adhesive strength of current collector after heat treatment A0 = adhesive strength of current collector before heat treatment

[0101] experiment Experiment 1 The performance of a current collector according to the invention having a first and second metal (Cu or Al) layer on a polyester (PET or PEN) film substrate was investigated using a commercially available cell type and specifications. The current collector had an ABC layer structure, where layer A was the first metal layer, layer B was the polyester film substrate, and layer C was the second metal layer. The thickness of each metal layer was 150 nm. The thickness of the polyester film substrate was 6 μm. The performance was compared with a current collector made of a metal foil (Cu or Al) with a thickness of 12 μm.

[0102] Four commercially available lithium-ion cells were studied based on the supplier's specifications. Example 1 is based on a Chevrolet Spake EV (2012) A123 pouch cell with C / LFP cell chemistry at 3.3V and 20Ah. Example 2 is based on a Toshiba SciB high power cell with LTO / NMC cell chemistry at 2.4V and 2.9Ah. Example 3 is based on an A123 cylindrical 18650 cell with C / LFP cell chemistry at 3.3V and 1.2Ah. Example 4 is based on a cylindrical 21700 cell with C / NMC cell chemistry at 3.9V and 3.8Ah.

[0103] The cell mass, energy density, and power density were determined for each commercially available cell equipped with either the current collector of the present invention (Examples 1-4) or the conventional foil current collector (Comparative Examples 1-4). The results are shown in Table 1 ("n / m" means "not measured").

[0104] As demonstrated by the data in Table 1, the current collectors of the present invention enable the formation of cells having significantly reduced mass compared to cells made with conventional current collectors made of metal foils. Thus, by using the current collectors of the present invention, lithium ion batteries can be produced with reduced mass, improved energy density, and improved power density. [Table 1]

[0105] Experiment 2 A series of biaxially oriented films were made to investigate the effect of post-stretch heat treatment on thermal expansion. Comparative Example 5, Example 7, and Example 16 were PET films with a thickness of 6 μm, respectively. Comparative Example 6 was a PEN film with a thickness of 6 μm. The films were stretched simultaneously in MD and TD using the stretch ratios shown in Table 2. The biaxially stretched films were then annealed under dimensional constraint and then subjected to MD and TD relaxation according to the conditions shown in Table 2. Comparative Example 5, Example 7, and Example 16 were subjected to two relaxation steps, while Comparative Example 6 was subjected to one relaxation step. The thermal expansion in air at 200°C and the linear thermal expansion coefficient in both MD and TD were evaluated for each film, and the results are shown in Table 2 ("n / m" means "not measured"). Negative values ​​of thermal expansion indicate shrinkage. Plots of the thermal expansion from 32°C to 200°C for each of Examples 5-7 are shown in Figures 2A-2C, respectively. [Table 2]

[0106] As shown in Table 2 and Figure 2, the thermal expansion behavior of the films is a function of the degree of relaxation and the temperature used during the relaxation step (or relaxation steps). For example, the film of Comparative Example 5 (Figure 2A) shows TD expansion below about 180°C, which corresponds to the highest temperature used during the TD relaxation step, and then shows TD shrinkage at higher temperatures. In contrast, the film of Example 7 (Figure 2C) and the film of Example 16 show TD expansion at 200°C, which is due to the higher temperatures used during the TD relaxation step.

[0107] Additionally, the film of Comparative Example 5 exhibits negative CLTE in both TD and MD over the range of 32° C. to 200° C., respectively, because it exhibits TD and MD shrinkage at higher temperatures. In contrast, the film of Example 7 (FIG. 2C) advantageously exhibits positive CLTE in both TD and MD over the range of 32° C. to 200° C., respectively, because the film exhibits TD and MD expansion over this temperature range, including as high as 200° C.

[0108] Experiment 3 A series of current collectors were made by metallizing a series of biaxially oriented polyester films. The polymers and thicknesses of the biaxially oriented substrates are shown in Table 3. Prior to deposition of the metal layer, the biaxially oriented films were simultaneously stretched in MD and TD using the stretch ratios shown in Table 3, and then relaxed in MD and TD using the conditions shown in Table 3 ("-" means that the film was not subjected to said relaxation step). The total time of the relaxation step (or relaxation steps) was 0.4-4.7 seconds. Next, a metal layer of Al having a thickness of 40-91 nm (as shown in Table 3) was deposited on the first surface of the biaxially oriented substrate. Then, for both Comparative Examples 8-9 and Examples 11-12, a second metal layer of Al having the same thickness as the first metal layer was deposited on the second surface of the biaxially oriented substrate to provide a current collector with an ABC layer structure, where layer A is the first metal layer, layer B is the polyester film substrate, and layer C is the second metal layer. The thermal expansion of the films in MD and TD in air at 200° C. and the peel resistance of the current collector were measured as described herein and the results are shown in Table 3. [Table 3]

[0109] As demonstrated by the data in Table 3, current collectors in which the substrate layer exhibits positive thermal expansion in each of MD and TD provide surprisingly improved peel resistance when exposed to high temperatures. Each of the films of Examples 11 and 12 exhibits positive MD and TD expansion at 200°C, providing surprisingly improved peel resistance. In particular, the adhesive strength of the film is surprisingly retained after exposure to high temperatures, as the loss of adhesive strength is very small. Thus, overall, the adhesion observed after exposure to high temperatures remains high. In contrast, each of the films of Comparative Examples 8-10 exhibits at least MD shrinkage at 200°C, and at least 45% of the original adhesive strength is lost after exposure to high temperatures, resulting in poor peel resistance.

[0110] The sheet resistance of the film of Comparative Example 10 was measured as described herein. The sheet resistance was 0.9-2 Ωsq. -1 Therefore, the current collectors showed good sheet resistance. In particular, the current collectors with a higher metal layer thickness of about 88 nm showed a sheet resistance of 1 Ωsq. -1 Advantageously, a sheet resistance of less than 100 nm was achieved.

[0111] Reference experiment 4 A preliminary series of current collectors were made using a PEN polyester substrate layer and first and second Cu metal layers. The biaxially oriented PEN polyester film had a thickness of 6 μm. The film was simultaneously stretched in MD and TD with an MD stretch ratio of 3.35 and a TD stretch ratio of 3.55. The biaxially oriented PEN polyester film was then annealed under dimensional restraint and subjected to a TD relaxation of −1% at a temperature of 190° C. for 2.8 seconds. The thermal expansion of the film in MD and TD in air at 200° C. was measured as described herein and found to be −0.45 and 0.18, respectively.

[0112] To provide Comparative Examples 13 and 14, first and second Cu metal layers were deposited on biaxially oriented PEN polyester film using the virtual cathodic deposition process described above. Comparative Example 15 was a conventional metal foil made from Cu. Table 4 shows the thickness as well as the through film resistance (R), sheet resistance (Sheet R), breakdown current and temperature at breakdown measured as described herein. [Table 4]

[0113] The results in Table 4 demonstrate that current collectors based on metallized polymer films advantageously exhibit lower breakdown currents and temperatures compared to conventional metal foil current collectors, and therefore can prevent excessive current flow during use, thereby minimizing the risk of short circuits or heat propagation. The sheet resistance was low enough to allow good electrical conductivity in the plane of the copper layer. The present disclosure includes the following embodiments. <Embodiment 1> 1. A current collector comprising a biaxially oriented polymer substrate layer and a first metal layer on a surface of the polymer substrate layer, the polymer substrate layer exhibiting positive thermal expansion in air at 200° C. in each of the transverse direction (TD) and the machine direction (MD), the polymer substrate layer having a thickness of 12 μm or less, and the first metal layer having a thickness of 1000 nm or less. <Embodiment 2> 2. The current collector of embodiment 1, further comprising a second metal layer, the first metal layer and the second metal layer being on opposite sides of the polymeric substrate layer, and the second metal layer independently having a thickness of 1000 nm or less. <Embodiment 3> The current collector according to embodiment 1 or 2, wherein the polymer substrate layer has a thickness of 1.0 to 12.0 μm, preferably 2.0 to 8.0 μm, preferably 4.0 to 8.0 μm, preferably 4.0 to 6.0 μm. <Embodiment 4> 4. The current collector according to any one of embodiments 1 to 3, wherein the polymer substrate layer is a polyester substrate layer, and preferably the polyester is polyethylene terephthalate or polyethylene naphthalate. <Embodiment 5> The current collector according to any one of embodiments 1 to 4, wherein the polymer substrate layer exhibits a thermal expansion in air at 200° C. of more than 0% and not more than 3.0%, preferably 0.1% to 2.0%, and preferably 0.2% to 1.5%, in each of the transverse direction (TD) and the longitudinal direction (MD). <Embodiment 6> The polymer substrate layer is heated to a temperature of preferably 20×10° C. in the range of 32° C. to 200° C. in each of the transverse direction (TD) and the machine direction (MD). -5 / ℃, preferably less than 17×10 -5 / ℃, preferably less than 10×10 -5 / ℃, preferably less than 9×10 -5 / ℃, preferably less than 8.5×10 -5 6. The current collector according to any one of embodiments 1 to 5, which exhibits a positive coefficient of linear thermal expansion (CLTE) of less than 1 / °C. <Embodiment 7> The current collector according to any one of embodiments 1 to 6, wherein the first metal layer (A), and, if present, the second metal layer (C), each independently have a thickness of 50 nm to 1000 nm, preferably 100 nm to 1000 nm, preferably 100 nm to 800 nm, preferably 150 nm to 700 nm. <Embodiment 8> The current collector according to any one of embodiments 1 to 7, wherein the first metal layer (A), and, if present, the second metal layer (C), each independently exhibit an isotropic thermal expansion in air at 200° C. of greater than 0% and not greater than 1.0%, preferably 0.25% to 0.75%, preferably 0.3% to 0.5%, and preferably the first metal layer (A) and the second metal layer (C) exhibit the same thermal expansion at 200° C. <Embodiment 9> The first metal layer (A), and, if present, the second metal layer (C), each independently have a melting point of 10×10 in air at 100° C. -6 / ℃~30×10 -6 / °C, preferably 12 x 10 -6 ℃~18×10 -6 9. The current collector according to any one of embodiments 1 to 8, which exhibits a positive coefficient of linear thermal expansion (CLTE) of 1 / °C. <Embodiment 10> 10. The current collector of any one of embodiments 1-9, wherein the first metal layer (A) and, if present, the second metal layer (C) each independently comprise at least one of aluminum, copper, nickel, titanium, silver, a nickel-copper alloy, or an aluminum-zirconium alloy, and preferably the first metal layer and the second metal layer are selected from the same material. <Embodiment 11> 11. The current collector of any one of embodiments 1 to 10, wherein the first metal layer and the second metal layer are both aluminum or copper. <Embodiment 12> 12. The current collector of any one of the preceding embodiments, wherein the adhesive strength between the metal layer and the polymeric substrate layer is at least 600 g / 25 mm, preferably at least about 700 g / 25 mm, and preferably at least about 800 g / 25 mm. <Embodiment 13> 0.01Ωsq -1 ~2.0Ωsq -1 , preferably 0.02Ωsq -1 ~2.5Ωsq -1 , preferably 0.02Ωsq -1 ~2.0Ωsq -1 , preferably 0.02Ωsq -1 ~1.5Ωsq -1 , preferably 0.05Ωsq -1 ~1.0Ωsq -1 13. The current collector according to any one of embodiments 1 to 12, which exhibits a sheet resistance of <Embodiment 14> 14. The current collector of any one of embodiments 1 to 13, exhibiting a breakdown current of about 30 A or less and / or a breakdown temperature of about 300° C. or less. <Embodiment 15> The current collector of embodiment 2, or any one of embodiments 3 to 14 when dependent on embodiment 2, further comprising at least one tab connecting the first metal layer and the second metal layer. <Embodiment 16> 16. The current collector of any one of the preceding embodiments, wherein the polymeric substrate layer comprises channels extending from the first surface to the opposing second surface, and (i) both sides of the channels are at least partially coated with at least one metal, and / or (ii) the channels are at least partially filled with at least one metal. <Embodiment 17> A method for producing a current collector according to any one of embodiments 1 to 16, comprising the steps of: (i) forming a biaxially oriented polymeric substrate layer; and (ii) depositing a metal on a first surface of the substrate layer to form a first metal layer; The method comprising: <Embodiment 18> (iii) depositing a metal on a second surface of the substrate layer to form a second metal layer; 18. The method of embodiment 17, wherein the layer sequence is first metal layer / polymeric substrate layer / second metal layer. <Embodiment 19> 19. The method of embodiment 17 or embodiment 18, wherein step (i) comprises extruding a layer of molten polymer and subjecting the extrudate to biaxial orientation at a temperature above the glass transition temperature(s) of the polymer, preferably the biaxial orientation is simultaneous biaxial orientation, preferably such that the dimension of the oriented film is stretched to 2 to 5 times its original dimension in each direction of stretching. <Embodiment 20> Step (i) is performed at a temperature above the glass transition temperature(s) of the polymer but above its melting temperature (T M dimensionally stabilizing the biaxially stretched film by annealing under dimensional support at a temperature below about T M -80℃~approx.T M The method according to embodiment 17, embodiment 18, or embodiment 19, wherein the temperature is in the range of -10°C, preferably in the range of about 200 to about 245°C, preferably in the range of about 220 to about 240°C. <Embodiment 21> 21. The method according to embodiment 17, 18, 19 or 20, wherein step (i) comprises subjecting the biaxially stretched film to dimensional relaxation in both the transverse and longitudinal directions, the relaxation degree being about 0.5 to about 5.0%, preferably about 1.0 to about 4.0%, preferably about 1.0 to 3.0%, preferably about 1.0 to about 2.0%, in each of the transverse and longitudinal directions, preferably the relaxation degrees in the longitudinal and transverse directions are not the same, preferably the temperature of the relaxation step is equal to or lower than the temperature of the preceding annealing step, and preferably about 200° C. to about 245° C., preferably about 200° C. to about 240° C., preferably about 210° C. to about 230° C., preferably about 215° C. to about 230° C., and if the method comprises an annealing step according to embodiment 20, the dimensional relaxation is performed thereafter. <Embodiment 22> The method according to embodiment 21, wherein step (i) comprises a second relaxation step after the relaxation step according to embodiment 21, said second relaxation step being carried out at a lower temperature than the relaxation step according to embodiment 21, preferably at least about 5°C lower, and preferably at a temperature in the range of about 195°C to about 240°C, preferably about 195°C to about 235°C, preferably about 195°C to about 230°C, preferably about 195°C to about 220°C. <Embodiment 23> 23. The method according to any one of embodiments 17 to 22, comprising subjecting the exposed surface of the polymeric substrate layer to a surface modification treatment, said treatment step being carried out after step (i) and before step (ii), preferably said treatment comprising subjecting the exposed surface of the polymeric substrate layer to a plasma treatment, preferably a corona discharge. <Embodiment 24> 24. The method of any one of embodiments 17-23, wherein step (ii) and / or step (iii) comprises depositing the metal using thermal evaporative deposition, electron beam evaporative deposition, or virtual cathode evaporation. <Embodiment 25> A current collector obtained by the method according to any one of embodiments 17 to 24. <Embodiment 26> 26. Use of a biaxially oriented polymer film as a substrate in a current collector further comprising a first metal layer, the use being for imparting improved adhesive strength and peel resistance between the substrate and a metal layer, the polymer substrate layer exhibiting positive thermal expansion in air at 200° C. in each of the transverse direction (TD) and machine direction (MD), the polymer substrate layer having a thickness of 12 μm or less, and the first metal layer having a thickness of 1000 nm or less, preferably the current collector being as described in any of embodiments 1-16 or 25. <Embodiment 27> 26. A battery comprising an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector, and a cathode current collector, wherein at least one of the current collectors is the current collector of any one of embodiments 1-16 or 25. <Embodiment 28> 28. The battery of embodiment 27, wherein the battery is a lithium ion battery. <Embodiment 29> 29. The battery of embodiment 27 or embodiment 28, wherein the anode material is coated on the anode current collector, and the anode current collector is the current collector of any one of embodiments 1-16 or 25. <Embodiment 30> 30. The battery of embodiment 27, 28, or 29, wherein the cathode material is coated on the cathode current collector, and the cathode current collector is the current collector of any one of embodiments 1-16 or 25. <Embodiment 31> 30. Use of the current collector of any one of embodiments 1 to 16 or 25 in the battery of embodiment 27, 28 or 29. <Embodiment 32> A method for producing a battery according to any one of embodiments 27 to 30, comprising the steps of: (iii) preparing or obtaining the current collector according to any one of embodiments 1 to 16 or 25; (iv) assembling the battery, the battery comprising an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector, and a cathode current collector, at least one of the current collectors being the current collector obtained from step (i); The method comprising:

Claims

1. 1. A current collector comprising a biaxially oriented polyester substrate layer, a first metal layer on a face of the polyester substrate layer, and a second metal layer, the layer sequence being first metal layer / polyester substrate layer / second metal layer, the polyester substrate layer exhibiting positive thermal expansion in air at 200° C. in each of the transverse direction (TD) and machine direction (MD), the thermal expansion being measured according to a method of the specification, the polyester substrate layer having a thickness of 12 μm or less, the first metal layer having a thickness of 1000 nm or less, and the second metal layer independently having a thickness of 1000 nm or less.

2. 2. The current collector according to claim 1, wherein the polyester substrate layer has a thickness of 1.0 to 12.0 μm.

3. 2. The current collector of claim 1, wherein the polyester is polyethylene terephthalate or polyethylene naphthalate.

4. 2. The current collector of claim 1, wherein the polyester substrate layer exhibits a thermal expansion in air at 200° C. of greater than 0% and less than or equal to 3.0% in each of the transverse direction (TD) and the machine direction (MD).

5. 2. The current collector of claim 1, wherein the polyester base layer exhibits a positive coefficient of linear thermal expansion (CLTE) over a range of 32°C to 200°C in each of the transverse direction (TD) and the machine direction (MD), the CLTE being measured according to the method of the specification.

6. 2. The current collector according to claim 1, wherein the first metal layer (A) and the second metal layer (C) each independently have a thickness of 50 nm to 1000 nm.

7. 2. The current collector of claim 1, wherein the first metal layer (A) and the second metal layer (C) each independently exhibit an isotropic thermal expansion of greater than 0% to 1.0% or less in air at 200° C., wherein the isotropic thermal expansion means that the layers expand by the same amount in orthogonal directions.

8. The first metal layer (A) and the second metal layer (C) are each independently heated to 10×10 -6 / ℃~30×10 -6 2. The current collector of claim 1 , exhibiting a positive coefficient of linear thermal expansion (CLTE) of 1 / °C.

9. 2. The current collector of claim 1, wherein the first metal layer (A) and the second metal layer (C) each independently comprise at least one of aluminum, copper, nickel, titanium, silver, a nickel-copper alloy, or an aluminum-zirconium alloy.

10. 10. The current collector of claim 1, wherein the first metal layer and the second metal layer are both aluminum or copper.

11. 10. The current collector of claim 1, wherein the adhesive strength between a metal layer and the polyester substrate layer is at least 600 g / 25 mm, the adhesive strength being measured according to the method of the specification.

12. 0.01 Ω sq -1 10. The current collector of claim 1 exhibiting a sheet resistance of .about.2.0 .OMEGA.sq., said sheet resistance being measured according to the method herein.

13. 10. The current collector of claim 1, exhibiting a breakdown current of about 30 A or less and / or a breakdown temperature of about 300° C. or less, said breakdown current and breakdown temperature being measured according to the methods set forth herein.

14. 10. The current collector of claim 1 further comprising at least one tab connecting said first metal layer and said second metal layer.

15. 2. The current collector of claim 1, wherein the polyester substrate layer has a first surface and a second surface opposite the first surface, the polyester substrate layer including channels extending from the first surface to the opposite second surface, and (i) both sides of the channels are at least partially coated with at least one metal, and / or (ii) the channels are at least partially filled with at least one metal.

16. A method for producing a current collector according to any one of claims 1 to 15, comprising the steps of: (i) forming a biaxially oriented polyester substrate layer; (ii) depositing a metal on a first surface of the substrate layer to form a first metal layer; (iii) depositing a metal on a second surface of the substrate layer to form a second metal layer; Including, The method, wherein the layer sequence is first metal layer / polyester substrate layer / second metal layer.

17. 17. The method of claim 16, wherein step (i) comprises extruding a layer of molten polyester to obtain an extrudate and subjecting said extrudate to biaxial orientation at a temperature above the glass transition temperature(s) of said polyester.

18. Step (i) is carried out at a temperature above the glass transition temperature (T M 20. The method of claim 16, further comprising dimensionally stabilizing the biaxially stretched film by annealing the film under dimensional support at a temperature below 200.degree.

19. 17. The method of claim 16, wherein step (i) comprises subjecting the biaxially stretched film to dimensional relaxation in both the transverse and longitudinal directions, the degree of relaxation being from about 0.5 to about 5.0% in each of the transverse and longitudinal directions.

20. 20. The method of claim 19, wherein step (i) comprises a second relaxation step after the relaxation step of claim 19, said second relaxation step being carried out at a lower temperature than the relaxation step of claim 19.

21. 17. The method of claim 16, comprising subjecting the exposed surface of the polyester substrate layer to a surface modification treatment, said treatment step occurring after step (i) and before step (ii).

22. 17. The method of claim 16, wherein step (ii) and / or step (iii) comprises depositing the metal using thermal evaporative deposition, electron beam evaporative deposition, or virtual cathode evaporation.

23. 1. Use of a biaxially oriented polyester film as a substrate in a current collector further comprising a first metal layer and a second metal layer, the use being for imparting improved adhesive strength and peel resistance between the substrate and the metal layers, the polyester substrate layer exhibiting positive thermal expansion in air at 200° C. in each of the transverse direction (TD) and machine direction (MD), the thermal expansion being measured according to the method of the specification, the polyester substrate layer having a thickness of 12 μm or less, the first metal layer having a thickness of 1000 nm or less, and the second metal layer independently having a thickness of 1000 nm or less.

24. 13. A battery comprising an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector, and a cathode current collector, wherein at least one of the current collectors is the current collector described in claim 1.

25. 25. The battery of claim 24, wherein the battery is a lithium ion battery.

26. The battery of claim 24, wherein the anode material is coated on the anode current collector, the anode current collector being a current collector according to any one of claims 1 to 15.

27. The battery of claim 24, wherein the cathode material is coated on the cathode current collector, the cathode current collector being a current collector according to any one of claims 1 to 15.

28. Use of a current collector according to any one of claims 1 to 15 in a battery according to claim 24.

29. 25. A method for producing the battery of claim 24, comprising the steps of: (i) preparing or obtaining a current collector according to any one of claims 1 to 15; (ii) assembling the battery, the battery comprising an anode material, a cathode material, a separator between the anode material and the cathode material, an anode current collector, and a cathode current collector, at least one of the current collectors being the current collector obtained from step (i); The method comprising:

Citation Information

Patent Citations

  • Film for secondary battery electrode

    JP1998040920A

  • Battery and its manufacturing method

    JP2008300336A

  • Biaxially oriented polyester film for power storage element electrode

    JP2014220187A

  • Non-aqueous electrolyte battery

    WO2012127561A1